2004
DOI: 10.1385/bter:98:2:119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Statins on Oxidative Stress

Abstract: Free oxygen radicals and insufficient antioxidant enzymes have been implicated in the pathogenesis of hypercholesterolemia (HC). Trace elements function as cofactors in antioxidant enzymes. Antioxidant system and trace elements were investigated in many different studies including HC, but these subjects have not been investigated as a whole in these patients. The aim of the present study was to investigate the antioxidative system and trace elements in hypercholesterolemic patients given fluvastatin therapy. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 30 publications
4
42
1
4
Order By: Relevance
“…Recent clinical trials demonstrated that PPAR-␣ or PPAR-␥ agonist improved the outcome of atherosclerotic heart disease (10,14), whereas dual-PPAR agonist did not (34). In addition, statins improved insulin resistance (41) and antioxidant activities, including the restoration of Cu/ZnSOD activity (48), prevented the development of diabetes, reduced lipid levels (13,38), and improved clinical outcome in patients with hypercholesterolemia (1). These results, taken together with those of the present study, indicate that pitavastatin may selectively activate PPAR-␥ and Cu/ ZnSOD in hypercholesterolemia as pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical trials demonstrated that PPAR-␣ or PPAR-␥ agonist improved the outcome of atherosclerotic heart disease (10,14), whereas dual-PPAR agonist did not (34). In addition, statins improved insulin resistance (41) and antioxidant activities, including the restoration of Cu/ZnSOD activity (48), prevented the development of diabetes, reduced lipid levels (13,38), and improved clinical outcome in patients with hypercholesterolemia (1). These results, taken together with those of the present study, indicate that pitavastatin may selectively activate PPAR-␥ and Cu/ ZnSOD in hypercholesterolemia as pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…These "pleiotropic effects" of statins include improvement of endothelial function, antithrombotic actions, plaque stabilization, reduction of the vascular inflammatory process, and an antioxidant function through the inhibition of NAD(P)H oxidase or the increase in SOD activity (3,6,26,32). Statins are also reported to improve insulin resistance (41) and antioxidant properties, including the restoration of Cu/ZnSOD activity (48), and prevent the development of diabetes in patients with hypercholesterolemia (13,38). Taken together, these observations allow one to assume that statins may have antiatherogenic actions through PPAR and Cu/ZnSOD activation, in addition to antidyslipidemic actions.…”
mentioning
confidence: 99%
“…The anti-inflammatory effect may also be related to decreased graft rejection via its immunomodulatory effects and the inhibition of factors that activate the inflammatory cascade (12) . The administration of fluvastatin in dyslipidemic patients induces reduced lipid levels and increased antioxidant protection by reducing the markers of oxidative injury (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested statins protect the vascular endothelium from oxidative damage 182 Risk Factors for Age-related Macular Degeneration…”
Section: -181mentioning
confidence: 99%